2010
DOI: 10.3855/jidc.1052
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection due to Aeromonas spp., a lesser known causative bacterium

Abstract: This item has no abstract. Follow the link below to access the full text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In the English-language articles, previous reported cases about Aeromonas species related urinary tract infection were caused by A. hydrophila, A. veronii biotype sobria, Aeromonas popoffii, A. caviae, Aeromonas schubertii, 2e6 and Mandal et al showed that A. caviae was the most common species which caused urinary tract infection in four patients in their series of 7 cases. 2 In contrast, A. hydrophila causes more than half of the infections in this series. Moreover, it is the first time to report that mixed genitourinary infection caused by A. caviae and A. veronii at the same time.…”
mentioning
confidence: 81%
“…In the English-language articles, previous reported cases about Aeromonas species related urinary tract infection were caused by A. hydrophila, A. veronii biotype sobria, Aeromonas popoffii, A. caviae, Aeromonas schubertii, 2e6 and Mandal et al showed that A. caviae was the most common species which caused urinary tract infection in four patients in their series of 7 cases. 2 In contrast, A. hydrophila causes more than half of the infections in this series. Moreover, it is the first time to report that mixed genitourinary infection caused by A. caviae and A. veronii at the same time.…”
mentioning
confidence: 81%
“…Treatment with carbapenems is effective, although some cases of pneumonia have been fatal [223]. Aeromonas were also described as a causal agent in urinary tract infections [5,224,225]. The majority of the cases were reported in patients with various underlying diseases, such as spina bifida, bilateral renal dilatation, and diabetes mellitus.…”
Section: Other Infectionsmentioning
confidence: 99%
“…Earlier studies have reflected on the drug resistance mechanisms in this group. In a study from Kolkata, India, it was observed that many of the Aeromonas strains were resistant to furazolidone, quinolones and cephalosporins [ 5 ]. In fact, multiple drug resistance among Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility to the antibiotics varies according to the geographical area and the species of Aeromonas tested. Most of the isolates are generally susceptible to tetracyclines and quinolones though development of increasing resistance to third generation cephalosporins due to the production of beta-lactamases and extended spectrum beta-lactamases (ESBLs) has been noted in the recent years [ 2 , 3 , 5 ]. The current study was undertaken to characterize the third generation cephalosporin-resistant strains of Aeromonas spp.…”
Section: Introductionmentioning
confidence: 99%